2019
DOI: 10.14742/ajet.3795
|View full text |Cite
|
Sign up to set email alerts
|

Stop! Grammar time: University students’ perceptions of the automated feedback program Grammarly

Abstract: Universities are increasingly looking towards online technology to assist their students. Grammarly advertises itself as the world’s most accurate online grammar checker, yet little research exists on its performance as a feedback tool in universities. This paper reports on a study investigating students’ perceptions of Grammarly when used in conjunction with advice from an academic learning advisor. Using a mixed methods sequential explanatory design, the study compared one group of students’ responses to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 21 publications
(27 reference statements)
1
76
0
2
Order By: Relevance
“…They found large discrepancies: the instructor provided more and better-quality feedback. Others focused on instructional applications of automated feedback (e.g., Cavaleri & Dianati, 2016;O'Neill & Russell, 2019a, 2019bVentayen & Orlanda-Ventayen, 2018). A study by O'Neill and Russell (2019b) found that the Grammarly group responded more positively and was better satisfied with the grammar advice than the non-Grammarly group.…”
Section: Affordances and Limitations Of Automated Feedback In L2 Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…They found large discrepancies: the instructor provided more and better-quality feedback. Others focused on instructional applications of automated feedback (e.g., Cavaleri & Dianati, 2016;O'Neill & Russell, 2019a, 2019bVentayen & Orlanda-Ventayen, 2018). A study by O'Neill and Russell (2019b) found that the Grammarly group responded more positively and was better satisfied with the grammar advice than the non-Grammarly group.…”
Section: Affordances and Limitations Of Automated Feedback In L2 Writingmentioning
confidence: 99%
“…Others focused on instructional applications of automated feedback (e.g., Cavaleri & Dianati, 2016;O'Neill & Russell, 2019a, 2019bVentayen & Orlanda-Ventayen, 2018). A study by O'Neill and Russell (2019b) found that the Grammarly group responded more positively and was better satisfied with the grammar advice than the non-Grammarly group. Another study, by Qassemzadeh and Soleimani (2016) found that both teacher and Grammarly feedback positively influenced students' study of passive structures.…”
Section: Affordances and Limitations Of Automated Feedback In L2 Writingmentioning
confidence: 99%
“…Their evidence of robotic input innovation in Australian tertiary organizations has focused on examining language structures. According to ONeill & Russell (2019) checking this machine regarding the views of students being lazy to think critically is right. They suggest that this Grammarly application be used as an input tool for academic-related tasks.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of literature has revealed the practical functionality of CEA in producing constructive comments (Dembsey, 2017;O'Neill & Russell, 2019), offering explicit over generic feedback (Ranalli, 2018), assisting the reduction in the number of errors (i.e., related to vocabulary, grammar, spelling; Ghufron & Rosyida, 2018), and offering more suitable local surface-level errors (e.g., articles, preposition, and verb-noun agreement) (Bailey & Lee, 2020), and easing the assessment and evaluation process (Al-Ahdal, 2020), including self-assessment to motivate learners (Dikli & Bleyle, 2014).…”
Section: Computer-aided Error Analysis (Cea)mentioning
confidence: 99%